Simulation of flow and soot particle distribution in wall-flow DPF based on lattice Boltzmann method. (20th July 2019) - Kong, Xiangjin; Li, Zhijun; Shen, Boxi; Wu, Yue; Zhang, Yanke; Cai, Dong
Graphical abstract: Highlights: The LB-CA model is developed to investigate the flow and soot loading. Non-virtual porous structure wall is considered in the filtration process. The effects of upstream velocities on flow field and soot distribution are studied. The distribution of soot particles is also simulated by LB-Lagrangian model. The deposited particles dynamic evolution and its effect on flow field are studied. Abstract: A two-dimensional mesoscopic gas-solid two-phase flow model has been developed to investigate the flow and soot loading in the micro-channel of diesel particulate filters. Soot particle size examined is in the range of 10 nm–1 µm. The flow is solved by an incompressible lattice Boltzmann model and the transport of solid particles is described by the cell automation probabilistic model. The lattice Boltzmann-cell automation probabilistic model (LB-CA model) is validated with the results of previous studies. The effects of different upstream velocities on the flow field in channels are investigated. The distribution and deposition of soot particles with different sizes in clean channels are simulated based on the LB-CA method and the LB-Lagrangian method respectively. The effects of deposited soot particles on flow field are evaluated in real soot particle capture process. The results show that the distributions of velocity field and pressure field in the channel are significantly affected by the upstream velocity. Compared with the effect of the particle size, the upstream velocity is more influential on the particle deposition distributions. The profiles of deposition distribution from the LB-CA method are in close agreement with those from the LB-Lagrangian method. The deposition distributions of particles with different diameters at the top of the porous wall are similar to the distributions of wall velocity along the channel length. Generally, the deposited soot particles increase the axial pressure and decrease the axial velocity in the inlet channel. The evolution trend of the areas where wall velocity undergoes changes is consistent with that of the solid nodes made of the captured soot particles.